CGIAR submission of its views on the tenth technical expert dialogue and the second meeting under the ad hoc work programme on the new collective quantified goal on climate finance - Chilambe, Pedro; Mukherji, Aditi (CGIAR System Organization, 2024)
The ninth Technical Expert Dialogue (TED9) and the first meeting of the ad-hoc work program on the New Collective Quantified Goal (NCQG) on climate finance marked significant progress in structuring the future of climate finance under the Paris Agreement. The NCQG aims to enhance the predictability, transparency, and adequacy of financial flows to support developing countries in their climate actions. CGIAR acknowledges the critical discussions and inputs provided by various parties and the deliberations by parties during the ad-hoc work programme meeting in Cartagena Colombia, particularly focusing on the layers of the NCQG from the definition of climate finance to the financial instruments to be employed, as components of structure and sources. Building on the discussions that took place at the ninth Technical Expert Dialogue, the CGIAR through this submission submits its views on the tenth Technical Expert Dialogue and the second meeting under the ad hoc work programme on the NCQG, particularly around the issues of sources, structure, timeframe and sub- goals.